2016
DOI: 10.3847/0004-637x/830/1/24
|View full text |Cite
|
Sign up to set email alerts
|

The Search for Signatures of Transient Mass Loss in Active Stars

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 39 publications
1
54
0
Order By: Relevance
“…Our new method of proton flux estimation due to stellar flares has important limitations, but it will be useful until advancements are made in the indirect detection of particles from stellar eruptive events (e.g., coronal dimming or Type II or III radio bursts; Crosley et al 2016;Harra et al 2016) or in our understanding of particle acceleration under kilogauss magnetic field strengths. The scaling relations are statistical and are relatively inaccurate for individual flares.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our new method of proton flux estimation due to stellar flares has important limitations, but it will be useful until advancements are made in the indirect detection of particles from stellar eruptive events (e.g., coronal dimming or Type II or III radio bursts; Crosley et al 2016;Harra et al 2016) or in our understanding of particle acceleration under kilogauss magnetic field strengths. The scaling relations are statistical and are relatively inaccurate for individual flares.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%
“…Coronal dimming, when EUV emission lines dim after part of the corona has been evacuated from a CME (Mason et al 2014), was not observed by the Extreme UltraViolet Explorer (EUVE), likely due to insufficient sensitivity. Type II radio bursts that trace shocks associated with CMEs (Winter & Ledbetter 2015) are being searched for but have not yet been detected on other stars (Crosley et al 2016), but other possible kinematic signatures of CMEs in observed M dwarf flares have been detected (e.g., Houdebine et al 1990;Cully et al 1994;Fuhrmeister & Schmitt 2004). Type III radio bursts are caused by the acceleration of suprathermal electrons from solar active regions and have been detected on the M3 dwarf AD Leo (Osten & Bastian 2006).…”
Section: Flares and Energetic Particlesmentioning
confidence: 99%
“…Such signals could be detected, e.g., with the Low Frequency Array (LOFAR) (e.g., Crosley et al 2016). However, the Sun will remain for a long time our only source of direct information on CMEs and the studies on CME-induced effects on exoplanets have to rely largely on scaling laws derived using flare-CME and CME-ICME relationships from the Sun and our Solar System.…”
Section: Icmes Beyond the Solar Systemmentioning
confidence: 99%
“…There are multiple measurements of time-variable outflows from cool stars (Houdebine et al 1990;Cully et al 1994;Fuhrmeister & Schmitt 2004;Leitzinger et al 2011;Dupree et al 2014;Vida et al 2016;Korhonen et al 2017), but it is not yet clear whether these should be interpreted as magnetically driven events analogous to solar CMEs. It is possible that observing the extrasolar equivalents of Type II radio bursts (Crosley et al 2016) or the polarization signatures of off-limb prominences (Felipe et al 2017) could be promising avenues toward the goal of definitive exo-CME detection.…”
Section: Introductionmentioning
confidence: 99%